Faktor-Faktor Motivasi Pekerja Konstruksi Menurut Teori Kebutuhan Abraham H Maslow (Proyek Smart Building Pusdiklatwas BPKP) - Viliona Rahaya (Universitas Kristen Indonesia Paulus, 2025)
Labor productivity is a primary focus of productivity in the construction sector. The majority of workers in a project come from the same or nearby locations, and most of their skills are inherited from their predecessors. This research aims to identify the main factors of motivation for construction workers and factors that can increase their motivation. Primary data collection was carried out by distributing and completing questionnaires from respondents. Data analysis used SPSS software. The findings of this study indicate that the main priority affecting the motivation of construction project workers is fulfilling physiological needs, especially a good salary. Factors that increase worker motivation on projects include family support, recognition of work results, clear job targets, and construction safety and health programs.